Papillomavirus Microbicidal Activities of High-Molecular-Weight Cellulose Sulfate, Dextran Sulfate, and Polystyrene Sulfonate - Christensen, Neil D. (American Society for Microbiology, 2001)
The high-molecular-weight sulfated or sulfonated polysaccharides or polymers cellulose sulfate, dextran sulfate, and polystyrene sulfonate were tested for microbicidal activity against bovine papillomavirus type 1 (BPV-1) and human papillomavirus type 11 (HPV-11) and type 40 (HPV-40). In vitro assays included the BPV-1-induced focus-forming assay and transient infection of human A431 cells with HPVs. The compounds were tested for microbicidal activity directly by preincubation with virus prior to addition to cell cultures and indirectly by addition of virus to compound-treated cells and to virus-coated cells to test inactivation of the virus after virus-cell binding. The data indicated that all three compounds showed direct microbicidal activity with 50% effective concentrations between 10 to 100 μg/ml. These concentrations were nontoxic to cell cultures for both assays. When a clone of C127 cells was tested for microbicidal activity, approximately 10-fold-less compound was required to achieve a 50% reduction in BPV-1-induced foci than for the uncloned parental C127 cells. Pretreatment of cells with compound prior to addition of virus also demonstrated strong microbicidal activity with dextran sulfate and polystyrene sulfonate, but cellulose sulfate required several orders of magnitude more compound for virus inactivation. Polystyrene sulfonate prevented subsequent infection of HPV-11 after virus-cell binding, and this inactivation was observed up to 4 h after addition of virus. These data indicate that the polysulfated and polysulfonated compounds may be useful nontoxic microbicidal compounds that are active against a variety of sexually transmitted disease agents including papillomaviruses.